The Impact of Parental Education on Children’s English Language Success in Rural Nepal: Insights from Krishnapur Municipality - Paneru, Narendra Raj; Bohara, Bhuban Bahadur (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This study examines the relationship between parental education levels and children’s English language proficiency, focusing on the role of parental involvement in academic success. Conducted in Krishnapur Municipality, Nepal, the research included 10 participants: four primary-grade students, their parents, and two teachers. Using semi-structured interviews and thematic analysis, the study found a strong positive correlation between parental education and children’s academic performance. Educated parents provided structured learning environments, assisted with assignments, and motivated their children, fostering better English proficiency. In contrast, parents with limited education faced challenges in supporting their children due to time constraints, socio-economic barriers, and lack of resources. These findings highlight the critical role of parental education in overcoming educational inequities and enhancing learning outcomes, especially in rural contexts. The study recommends targeted interventions, such as workshops and training programs, to empower parents and improve their engagement in their children’s education.